Answer:
Please check the explanation.
Step-by-step explanation:
We know that when y varies directly with x, we get the equation
y ∝ x
y = kx
k = y/x
where 'k' is called the 'constant of direct variation'.
We are given that x = -2 and y = -2
Thus,
The equation is:
y = kx
substituting x = -2 and y = -2
-2 = k(-2)
-2 = -2k
We can further simplify the equation to determine the value of 'k'
so
dividing the equation by -2
-2/-2 = -2k/-2
1 = k
Therefore, the value of k = 1
Thus, the equation becomes
y = kx
substituting k = 1 in the equation
y = (1)x
y = x
Therefore, an equation that relates x and y is:
y = x